Concept of ‘Regular Remuneration’ and ‘Employee Remuneration’ Resulting from Their Personal Wage Classification Based on an Hourly or Monthly Rate Within the Meaning of Article 151¹ §§ 1 and 3 LC in The Light of the Supreme Court Case Law and Employment L (Ius Novum, 2025)
The article discusses the principles of calculating remuneration for overtime work under the Polish Labour Code and in light of recent Supreme Court case law. The author analyses the dual structure of compensation for overtime work: regular remuneration and the overtime supplement, highlighting their distinct legal and economic functions. Particular attention is paid to the question of which remuneration components may be included as part of ‘regular remuneration’ within the meaning of Article 151¹ § 1 of the Labour Code. The article also includes de lege ferenda proposals, advocating for a statutory definition of ‘regular remuneration’ to enhance transparency and ensure the adequacy of the remuneration system.